CHARACTERIZATION OF DOMESTIC GREYWATER FOR CONSTRUCTED WETLAND TREATMENT AND NON-POTABLE REUSE IN A TROPICAL PERI-URBAN RESIDENTIAL COMMUNITY - Ajoge, Hadiza Nuhu; Batagarawa, Rabia Lawal; Ahmed, Saminu; Ibrahim, Abdullahi; Obiekwe, Nwude Michael (FUDMA Journal of Sciences, 2026)
Increasing freshwater scarcity and rapid urbanization in tropical regions have intensified interest in greywater reuse as a sustainable water management strategy. Constructed wetlands offer a low-cost, nature-based solution for decentralized treatment; however, their effective design and optimization depend on a detailed understanding of influent greywater characteristics. Comprehensive characterization is therefore essential to guide system configuration, pretreatment requirements, and reuse risk assessment. This study characterized the physicochemical, nutrient, microbiological and trace-metal properties of domestic greywater generated from residential units at the National Water Resources Institute (NWRI), Kaduna, Nigeria, representing a tropical peri-urban environment. Composite samples were collected from bathrooms, kitchen sinks, wash basins and laundry outlets. Laboratory analyses were conducted using standard methods to determine organic strength indicators, solids content, nutrient levels, microbial loads, and selected heavy metals relevant to treatment design and reuse suitability. Greywater exhibited near-neutral pH (7.8) and moderate salinity (EC 2008 µS/cm). Organic pollution was high, with BOD₅ and COD concentrations of 286.45 mg/L and 537.42 mg/L, respectively and a BOD₅/COD ratio of 0.53, indicating good biodegradability. Suspended solids (237 mg/L) and turbidity (113 NTU) were elevated, suggesting pretreatment needs. Nutrient concentrations were appreciable, while sodium levels indicated potential irrigation constraints. Microbial indicators exceeded reuse limits, whereas trace metals remained low. The findings confirm that the greywater characteristics are suitable for treatment using small-scale Free Water Surface constructed wetlands, provided adequate pretreatment and post-treatment safeguards are incorporated to ensure safe non-potable reuse in tropical peri-urban communities.
Keywords: Domestic greywater; Greywater characterization; Constructed wetland treatment; Free water surface wetlands; Non-potable reuse